Supplementary material: CLT Walls: Assessing the Role of Vapour Barriers and Adaptive Membranes for Enhanced Building Durability ... - Jensen, Nickolaj Feldt (VBN, 2024)
Supplementary material for the conference paper "CLT Walls: Assessing the Role of Vapour Barriers and Adaptive Membranes for Enhanced Building Durability" submitted to the International Building Physics Conference IBPC 2024, 25-27 Juni, Toronto, Canada. The supplementary material contains the following: - Drawings of CLT wall models - WUFI Pro model report (describing the model build up and chosen settings) - WUFI Pro simulation results (in Excel format), presented for two sets of models: (1) with initial moisture set to default 80% RH, and (2) with initial moisture at saturation in the outermost 30 mm of the CLT element and remaining parts set to default RH. - VTT mould growth results (in Excel format). - The Danish climate data for Sjælsmark, used for the simulations. (Data for Kiruna, Bergen and Jyväskylä were obtained from the WUFI climate files database and cannot be uploaded as part of this dataset) ...